A copper alloy strip for vehicle connector and a preparation method thereof
By adding carbon nanostructure X and other alloy elements to the copper alloy strip and adopting advanced preparation technology, the problem of insufficient conductivity and corrosion resistance of traditional copper alloy strips is solved, and the comprehensive performance improvement of high conductivity and corrosion resistance is achieved, which is suitable for the high standard needs of modern automotive connectors.
Patent Information
- Application Number
- CN202510065872.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-16
AI Technical Summary
Traditional copper alloy strips are difficult to meet the high standard needs of modern automotive connectors in terms of conductivity and corrosion resistance, resulting in high power loss, high safety risks, and are prone to corrosion in harsh environments, affecting the reliability and safety of the connector.
By optimizing the alloy composition design, carbon nanostructure X (composite of carbon nanotubes and fullerenes) and appropriate amounts of yttrium, tin and phosphorus elements are added, and advanced preparation processes such as ultrasonic dispersion, vacuum refining and water-cooled copper mold casting are used to prepare copper alloy strips with high conductivity and corrosion resistance.
It significantly improves the conductivity and corrosion resistance of copper alloy strips, reduces the risk of electrical energy loss and corrosion, improves the reliability and durability of vehicle-mounted connectors, and ensures the stable operation of the automotive electrical system.
Smart Images

Figure QLYQS_2 
Figure QLYQS_4
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of copper alloy strips, in particular to a vehicle-mounted connector copper alloy strip and a preparation method thereof. Background Art
[0002] With the rapid development of the automotive industry, the number and complexity of on-board electronic devices are increasing. As a key connection component in the automotive electrical system, the performance requirements of on-board connectors are becoming increasingly stringent. Among many performance indicators, conductivity and corrosion resistance are particularly important to ensure the efficient and stable operation of on-board electronic systems.
[0003] Traditional copper alloy strips are gradually unable to meet the high standards of modern vehicle connectors in terms of conductivity and corrosion resistance. On the one hand, the conductivity of ordinary copper alloys is limited, which will cause large power losses during high current transmission, affecting the performance of vehicle electronic equipment and may cause safety hazards such as heating. On the other hand, in complex operating environments such as humidity, acid and alkali, high temperature, and long-term vibration, traditional copper alloy strips are prone to corrosion and oxidation, which will reduce the contact reliability of the connector and even cause connection failure, seriously affecting the overall performance and safety of the vehicle electrical system.
[0004] In order to overcome these problems, it is urgent to develop a new method for preparing copper alloy strips for vehicle connectors. By optimizing the alloy composition design and combining advanced preparation processes, the key performance indicators of copper alloy strips such as conductivity and corrosion resistance can be effectively improved, making them better adapted to the requirements of long-term stable operation of vehicle connectors in harsh environments, ensuring the reliability and durability of automotive electrical systems, and promoting the further development of the automotive industry towards intelligence, electrification, and high performance. Summary of the invention
[0005] The object of the present invention is to provide a vehicle-mounted connector copper alloy strip and a preparation method thereof, so as to solve the problems raised in the above-mentioned background technology.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] A vehicle-mounted connector copper alloy strip, the copper alloy strip comprising, by weight percentage, 0.04-0.1wt% Y, 1.5-3.5wt% Sn, 0.02-0.08wt% P, 0.5-2.5wt% carbon nanostructure X, and the remainder copper and unavoidable impurities;
[0008] The carbon nanostructure X is a composite of carbon nanotubes and fullerenes, and the mass ratio of the carbon nanotubes to the fullerenes is 2 to 4:1.
[0009] As a further solution of the present invention: the copper alloy strip comprises by weight percentage: Y: 0.06-0.08wt%, Sn: 2-3wt%, P: 0.04-0.06wt%, carbon nanostructure X: 1-2wt%, and the balance is copper and unavoidable impurities;
[0010] The carbon nanostructure X is a composite of carbon nanotubes and fullerenes, and the mass ratio of the carbon nanotubes to the fullerenes is 2.5-3.5:1.
[0011] As a further solution of the present invention: the copper alloy strip has a mass percentage composition of Y: 0.07wt%, Sn: 2.5wt%, P: 0.05wt%, carbon nanostructure X: 1.5wt%, and the balance is copper and unavoidable impurities;
[0012] The carbon nanostructure X is a composite of carbon nanotubes and fullerenes, and the mass ratio of the carbon nanotubes to the fullerenes is 3:1.
[0013] A method for preparing a copper alloy strip for a vehicle-mounted connector comprises the following steps:
[0014] S1. Preparation of carbon nanostructure X: Weigh carbon nanotubes and fullerenes according to the above ratio, and then place them together in an organic solvent, and use ultrasonic dispersion equipment to perform long-term ultrasonic treatment, the ultrasonic time is 2-4 hours, so that the carbon nanotubes and fullerenes are fully dispersed to form a uniform and stable carbon nanostructure X dispersion liquid, the concentration of which should be reasonably formulated according to the subsequent alloy addition amount;
[0015] S2. Melting: Put the electrolytic copper into the crucible of the vacuum induction furnace and evacuate it to - Pa, and then fill with high-purity argon gas until the pressure in the furnace is 0.03-0.05MPa, then turn on the electric furnace for heating, and control the heating rate at 8-12℃ / min. When the temperature reaches 1150-1200℃, the copper begins to melt. After the copper is completely melted, add yttrium master alloy, tin ingot and phosphor copper master alloy in sequence. After each element is added, use an electromagnetic stirring device to stir for 8-15 minutes to make the elements fully and evenly melted;
[0016] S3, adding carbon nanostructure X: when the temperature of the alloy melt obtained in S2 drops to 1100-1150° C., slowly add the pre-prepared and dispersed carbon nanostructure X dispersion into the alloy melt by drip irrigation, and continue stirring for 20-30 minutes by using an electromagnetic stirring device;
[0017] S4, refining: keep the vacuum degree in the furnace at - Pa, vacuum refining for 15-20 minutes to volatilize and remove the gas and low melting point impurities in the alloy liquid;
[0018] S5. Casting: Casting is performed using a water-cooled copper mold, which is preheated to 200-300° C. before use, and the refined alloy liquid is slowly poured into the mold through the bottom gate, with the pouring speed controlled at 80-150 mm / s;
[0019] S6. Homogenization treatment: Place the cast alloy billet into a resistance furnace surrounded by protective gas for homogenization treatment, control the heating rate at 6-8°C / min, heat to 750-800°C, and keep at this temperature for 8-10 hours;
[0020] S7, hot rolling: heat the alloy billet after homogenization treatment to 850-900℃ for 1.5-2.5 hours to make the alloy billet fully and evenly heated, and then hot roll it on a hot rolling mill, with the total processing rate controlled at 80-90%, and the final rolling temperature not less than 750℃;
[0021] S8. Cold rolling: After the hot-rolled strip is pickled and washed, it is cold rolled at room temperature. The total processing rate is controlled at 50-70%. During cold rolling, the reduction is controlled at 6-10% each time.
[0022] As a further solution of the present invention: in step S1, the organic solvent is N-methylpyrrolidone or dimethylformamide.
[0023] As a further solution of the present invention: in step S2, a layer of copper needs to be laid on the bottom of the crucible before smelting.
[0024] As a further solution of the present invention: in step S6, high-purity argon is used as the protective gas, and during the insulation process, the argon in the resistance furnace needs to be continuously maintained.
[0025] As a further solution of the present invention: in step S7, during hot rolling, the reduction amount is controlled at 12-20% each time, and the rolling passes are determined according to the final size requirements.
[0026] As a further solution of the present invention: in step S8, during the cold rolling process, multiple intermediate annealing is required, the annealing temperature is 450-550°C, the insulation time is 1.5-2.5 hours, and the gas in the furnace is protected by high-purity argon.
[0027] As a further solution of the present invention: after step S8 is completed, a low-temperature annealing treatment is performed, the annealing temperature is 250-350° C., and the insulation time is 1.5-3 hours.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] 1. Significant improvement in electrical performance
[0030] The addition of carbon nanostructure X (a composite of carbon nanotubes and fullerenes) is one of the key factors in improving conductivity. Carbon nanotubes have excellent electron transport properties, and their unique structure can provide a channel for rapid conduction of electrons. Fullerene molecules also have good electrical properties. After the two are combined, they work synergistically to form an effective conductive network in the copper matrix, greatly improving the conductivity of the alloy strip. Compared with traditional copper alloy strips, it can significantly reduce resistance and reduce the loss of electric energy during the transmission process of the vehicle connector, improve the energy utilization efficiency of the vehicle electronic system, reduce the safety hazards caused by resistance heating, and ensure the stable operation of electronic equipment.
[0031] An appropriate amount of tin (Sn) in the alloy also helps improve electrical conductivity. Tin can play a role in solid solution strengthening in the copper matrix, while optimizing the crystal structure, reducing the interference of lattice defects on electronic conduction, and further improving the overall electrical conductivity of the alloy.
[0032] 2. Enhanced corrosion resistance
[0033] The addition of yttrium (Y) can form a dense and stable oxide film on the surface of copper alloy. This oxide film can effectively block the contact between external corrosive media (such as humid air, acid and alkali solutions, etc.) and the copper matrix, preventing the copper alloy from oxidation and corrosion. In the vehicle environment, the car may face various harsh climates and road conditions. This corrosion resistance can ensure that the vehicle connector maintains good contact performance during long-term use, reduce poor contact or connection failure caused by corrosion, and improve the reliability and durability of the vehicle electronic system.
[0034] Phosphorus (P) elements can form a phosphating film with copper in the alloy, further enhancing the alloy's anti-corrosion protective layer. At the same time, phosphorus can also refine the grains, improve the alloy's organizational structure, and make the alloy's corrosion resistance more uniform and stable. Carbon nanostructure X itself also has a certain chemical stability, which can help enhance the overall corrosion resistance in the alloy. Through the synergistic effect with other elements, the copper alloy strip can better resist the corrosion factors in the complex use environment of the automobile.
[0035] In summary, the comprehensive advantages of the copper alloy strip in terms of conductivity and corrosion resistance enable it to stably and reliably realize the electrical connection function in the vehicle connector. High conductivity ensures the accuracy and efficiency of signal transmission, and corrosion resistance ensures long-term normal operation in harsh environments. The improvement of these comprehensive performances helps to reduce problems such as electrical failures, signal interference and connection failures in vehicle electronic systems, improve the stability and reliability of the entire vehicle electronic system, provide strong hardware support for the intelligent and electrified development of automobiles, enhance the adaptability and safety of automobiles under different working conditions, and reduce the maintenance cost of automobiles and downtime caused by failures. DETAILED DESCRIPTION
[0036] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] In the present invention, a vehicle-mounted connector copper alloy strip is provided, wherein the mass percentage composition of the copper alloy strip is: Y: 0.04-0.1wt%, Sn: 1.5-3.5wt%, P: 0.02-0.08wt%, carbon nanostructure X: 0.5-2.5wt%, and the balance is copper and unavoidable impurities;
[0038] The carbon nanostructure X is a composite of carbon nanotubes and fullerenes, and the mass ratio of the carbon nanotubes to the fullerenes is 2 to 4:1.
[0039] Among the above copper raw materials, electrolytic copper with a purity of not less than 99.9% should be selected as the main source of matrix material.
[0040] The preparation method of the above-mentioned vehicle-mounted connector copper alloy strip is:
[0041] S1. Preparation of carbon nanostructure X: Weigh carbon nanotubes and fullerenes according to the above ratio, and then place them together in an organic solvent, wherein the organic solvent is N-methylpyrrolidone or dimethylformamide, and perform long-term ultrasonic treatment using an ultrasonic dispersion device, wherein the ultrasonic treatment time is 2-4 hours, so that the carbon nanotubes and fullerenes are fully dispersed to form a uniform and stable carbon nanostructure X dispersion liquid, the concentration of which should be reasonably adjusted according to the subsequent alloy addition amount;
[0042] In the above process, the preparation of carbon nanotubes and fullerenes can be carried out in the following ways: carbon nanotubes can be prepared by chemical vapor deposition (CVD), with metal catalysts (such as iron, cobalt, etc.) as the catalytic core, and grown under high temperature and carbon source gas (such as methane, ethylene, etc.) to obtain carbon nanotubes with uniform diameter and complete structure. Fullerenes can be prepared by arc discharge method, under the protection of inert gas, to evaporate the carbon electrode and form fullerenes under specific conditions.
[0043] S2. Melting: Put the electrolytic copper into the crucible of the vacuum induction furnace and evacuate it to - Pa, and then fill with high-purity argon gas until the pressure in the furnace is 0.03-0.05MPa, providing an inert protective environment for smelting. Then turn on the electric furnace for heating, and control the heating rate at 8-12℃ / min. When the temperature reaches 1150-1200℃, the copper begins to melt. After the copper is completely melted, add yttrium master alloy, tin ingot and phosphor copper master alloy in turn. After adding each element, use an electromagnetic stirring device to stir for 8-15 minutes to make the elements fully and evenly melted. Before smelting, a layer of copper needs to be laid on the bottom of the crucible furnace in advance to prevent other alloy elements added later from directly contacting the bottom of the crucible and causing local overheating or uneven reaction.
[0044] S3, adding carbon nanostructure X: when the temperature of the alloy melt obtained in S2 drops to 1100-1150° C., the pre-prepared and dispersed carbon nanostructure X dispersion is slowly added to the alloy melt by drip irrigation, and the mixture is continuously stirred for 20-30 minutes by an electromagnetic stirring device. During the stirring process, the stirring speed and intensity should be controlled to ensure that the carbon nanostructure X can be evenly dispersed in the alloy liquid, and to avoid splashing of the melt or involving too much gas due to excessive stirring;
[0045] S4, refining: keep the vacuum degree in the furnace at - Pa, vacuum refining for 15-20 minutes to volatilize and remove the gas and low-melting-point impurities in the alloy liquid. During the refining process, the electromagnetic stirring device is continuously turned on with moderate stirring intensity to make it easier to discharge the impurities and gas inside the alloy liquid, further improving the purity of the alloy liquid. Through refining, defects such as inclusions and pores in the alloy can be effectively reduced, and the quality and performance of the alloy can be improved;
[0046] S5. Casting: Use a water-cooled copper mold for casting. The mold is preheated to 200-300°C before use. Preheating the mold can prevent the alloy liquid from generating excessive thermal stress due to rapid cooling during pouring, thereby avoiding casting defects such as cracks and shrinkage holes, and ensuring that the surface quality of the ingot is smooth and flat. The refined alloy liquid is slowly poured into the above mold through the bottom gate. The pouring speed is controlled at 80-150mm / s. During the pouring process, the alloy liquid flow must be kept stable to avoid splashing and gas entrapment, so as to ensure that the internal quality of the ingot is uniform;
[0047] S6. Homogenization treatment: Place the cast alloy billet in a resistance furnace surrounded by protective gas for homogenization treatment. Control the heating rate at 6-8℃ / min. After heating to 750-800℃, keep it at this temperature for 8-10 hours. Use high-purity argon as the protective gas. During the insulation process, the argon in the resistance furnace needs to be maintained continuously to prevent oxidation of the alloy surface and ensure that the quality and performance of the alloy are not affected. The purpose of homogenization treatment is to evenly distribute the components in the alloy and eliminate the component segregation phenomenon produced during the casting process.
[0048] S7, hot rolling: heat the alloy billet after homogenization treatment to 850-900℃ for 1.5-2.5 hours to make the alloy billet fully and evenly heated, and then hot rolling on a hot rolling mill, the total processing rate is controlled at 80-90%, the final rolling temperature is not less than 750℃, during hot rolling, the reduction is controlled at 12-20% each time, and the rolling pass is determined according to the final size requirements. During the hot working process, pay close attention to controlling the processing temperature, and ensure good formability of the alloy through reasonable process parameter setting and equipment regulation to avoid defects such as rolling cracks and folding;
[0049] S8. Cold rolling: After the hot-rolled strip is pickled and washed, it is cold rolled at room temperature. The total processing rate is controlled at 50-70%. During cold rolling, the reduction is controlled at 6-10% each time. During the cold rolling process, due to the existence of work hardening, the hardness of the strip will gradually increase and the plasticity will decrease. Therefore, multiple intermediate annealing can be carried out as needed. The annealing temperature is 450-550℃, the holding time is 1.5-2.5 hours, and the furnace gas is protected by high-purity argon. Intermediate annealing can eliminate work hardening, reduce the hardness of the material, and restore the plasticity, so as to continue cold processing and finally obtain the copper alloy strip with the required thickness and performance.
[0050] For products with extremely high requirements for conductivity and corrosion resistance, low-temperature annealing is required after cold rolling. The annealing temperature is 250-350℃ and the holding time is 1.5-3 hours. This step can eliminate the internal stress caused by cold working, stabilize the alloy structure, and further improve conductivity and corrosion resistance. By reasonably controlling the annealing temperature and time, its electrical and chemical properties can be optimized without significantly reducing the strength of the alloy to meet the needs of special application scenarios.
[0051] Example 1
[0052] In this embodiment, a copper alloy strip for a vehicle connector is provided, wherein the mass percentage composition of the copper alloy strip is: Y: 0.04wt%, Sn: 1.5wt%, P: 0.02wt%, carbon nanostructure X: 0.5wt%, and the balance is copper and unavoidable impurities;
[0053] The carbon nanostructure X is a composite of carbon nanotubes and fullerenes, and the mass ratio of the carbon nanotubes to the fullerenes is 2:1.
[0054] The method for preparing the copper alloy strip for the vehicle connector in the above embodiment is:
[0055] S1. Preparation of carbon nanostructure X: Weigh carbon nanotubes and fullerenes according to the above ratio, and then place them together in an organic solvent, wherein the organic solvent is N-methylpyrrolidone, and perform long-term ultrasonic treatment using an ultrasonic dispersion device, wherein the ultrasonic treatment time is 2 hours, so that the carbon nanotubes and fullerenes are fully dispersed to form a uniform and stable carbon nanostructure X dispersion liquid, the concentration of which should be reasonably adjusted according to the subsequent alloy addition amount;
[0056] S2. Melting: Put the electrolytic copper into the crucible of the vacuum induction furnace and evacuate it to Pa, and then fill with high-purity argon gas until the pressure in the furnace is 0.03MPa, then turn on the electric furnace for heating, and control the heating rate at 8℃ / min. When the temperature reaches 1150℃, copper begins to melt. After the copper is completely melted, add yttrium master alloy, tin ingot and phosphor copper master alloy in turn. After each element is added, use an electromagnetic stirring device to stir for 8 minutes to make the elements fully and evenly melted. Before smelting, a layer of copper needs to be laid on the bottom of the crucible furnace in advance;
[0057] S3, adding carbon nanostructure X: when the temperature of the alloy melt obtained in S2 drops to 1100° C., the pre-prepared and dispersed carbon nanostructure X dispersion is slowly added to the alloy melt by drip irrigation, and the mixture is continuously stirred for 20 minutes by an electromagnetic stirring device;
[0058] S4, refining: keep the vacuum degree in the furnace at Pa, vacuum refining for 15 minutes to volatilize and remove the gas and low melting point impurities in the alloy liquid;
[0059] S5. Casting: Casting is performed using a water-cooled copper mold, which is preheated to 200° C. before use, and the refined alloy liquid is slowly poured into the mold through the bottom gate, with the pouring speed controlled at 80 mm / s;
[0060] S6. Homogenization treatment: The cast alloy billet is placed in a resistance furnace surrounded by protective gas for homogenization treatment. The heating rate is controlled at 6°C / min. After the temperature is raised to 750°C, it is kept at this temperature for 8 hours. The protective gas is high-purity argon gas, and during the insulation process, the argon gas in the resistance furnace needs to be continuously maintained;
[0061] S7, hot rolling: the alloy billet after homogenization treatment is heated to 850°C for 1.5 hours to make the alloy billet fully and evenly heated, and then hot rolled on a hot rolling mill, the total processing rate is controlled at 80%, the final rolling temperature is not less than 750°C, during hot rolling, the reduction is controlled at 12% each time, and the rolling pass is determined according to the final size requirements;
[0062] S8, cold rolling: After the hot-rolled strip is pickled and washed, it is cold rolled at room temperature, and the total processing rate is controlled at 50%. During cold rolling, the reduction is controlled at 6% each time. During the cold rolling process, multiple intermediate annealing is required, the annealing temperature is 450℃, the holding time is 1.5 hours, and the furnace gas is protected by high-purity argon. After the cold rolling, low-temperature annealing is carried out, the annealing temperature is 250℃, and the holding time is 1.5 hours.
[0063] Example 2
[0064] In this embodiment, a vehicle-mounted connector copper alloy strip is provided, wherein the mass percentage composition of the copper alloy strip is: Y: 0.1wt%, Sn: 3.5wt%, P: 0.08wt%, carbon nanostructure X: 2.5wt%, and the balance is copper and unavoidable impurities;
[0065] The carbon nanostructure X is a composite of carbon nanotubes and fullerenes, and the mass ratio of the carbon nanotubes to the fullerenes is 4:1.
[0066] The preparation method of the above copper alloy strip is:
[0067] S1. Preparation of carbon nanostructure X: Weigh carbon nanotubes and fullerenes according to the above ratio, and then place them together in an organic solvent, wherein the organic solvent is N-methylpyrrolidone, and perform long-term ultrasonic treatment using an ultrasonic dispersion device, wherein the ultrasonic treatment time is 4 hours, so that the carbon nanotubes and fullerenes are fully dispersed to form a uniform and stable carbon nanostructure X dispersion liquid, the concentration of which should be reasonably adjusted according to the subsequent alloy addition amount;
[0068] S2. Melting: Put the electrolytic copper into the crucible of the vacuum induction furnace and evacuate it to Pa, and then fill with high-purity argon gas until the pressure in the furnace is 0.05MPa, then turn on the electric furnace for heating, and control the heating rate at 12℃ / min. When the temperature reaches 1200℃, copper begins to melt. After the copper is completely melted, add yttrium master alloy, tin ingot and phosphor copper master alloy in turn. After each element is added, use an electromagnetic stirring device to stir for 15 minutes to make the elements fully and evenly melted. Before smelting, a layer of copper needs to be laid on the bottom of the crucible furnace in advance;
[0069] S3, adding carbon nanostructure X: when the temperature of the alloy melt obtained in S2 drops to 1150° C., the pre-prepared and dispersed carbon nanostructure X dispersion is slowly added to the alloy melt by drip irrigation, and the mixture is continuously stirred for 30 minutes by an electromagnetic stirring device;
[0070] S4, refining: keep the vacuum degree in the furnace at Pa, vacuum refining for 20 minutes to volatilize and remove the gas and low-melting-point impurities in the alloy liquid;
[0071] S5. Casting: Casting is performed using a water-cooled copper mold, which is preheated to 300° C. before use, and the refined alloy liquid is slowly poured into the mold through the bottom gate, with the pouring speed controlled at 150 mm / s;
[0072] S6. Homogenization treatment: The cast alloy billet is placed in a resistance furnace surrounded by protective gas for homogenization treatment. The heating rate is controlled at 8°C / min. After the temperature is raised to 800°C, it is kept at this temperature for 10 hours. The protective gas is high-purity argon gas, and during the insulation process, the argon gas in the resistance furnace needs to be continuously maintained;
[0073] S7, hot rolling: the alloy billet after homogenization treatment is heated to 900°C for 2.5 hours to make the alloy billet fully and evenly heated, and then hot rolled on a hot rolling mill, the total processing rate is controlled at 90%, the final rolling temperature is not less than 750°C, during hot rolling, the reduction is controlled at 20% each time, and the rolling pass is determined according to the final size requirements;
[0074] S8, cold rolling: After the hot-rolled strip is pickled and washed, it is cold rolled at room temperature, and the total processing rate is controlled at 70%. During cold rolling, the reduction is controlled at 10% each time. During the cold rolling process, multiple intermediate annealing is required, the annealing temperature is 550℃, the holding time is 2.5 hours, and the furnace gas is protected by high-purity argon. After the cold rolling, low-temperature annealing is carried out, the annealing temperature is 350℃, and the holding time is 3 hours.
[0075] Example 3
[0076] In this embodiment, a vehicle-mounted connector copper alloy strip is provided, wherein the mass percentage composition of the copper alloy strip is: Y: 0.06wt%, Sn: 2wt%, P: 0.04wt%, carbon nanostructure X: 1wt%, and the balance is copper and unavoidable impurities;
[0077] The carbon nanostructure X is a composite of carbon nanotubes and fullerenes, and the mass ratio of the carbon nanotubes to the fullerenes is 2.5:1.
[0078] The preparation method of the above copper alloy strip is:
[0079] S1. Preparation of carbon nanostructure X: Weigh carbon nanotubes and fullerenes according to the above ratio, and then place them together in an organic solvent, wherein the organic solvent is N-methylpyrrolidone, and perform long-term ultrasonic treatment using an ultrasonic dispersion device, wherein the ultrasonic treatment time is 3 hours, so that the carbon nanotubes and fullerenes are fully dispersed to form a uniform and stable carbon nanostructure X dispersion liquid, the concentration of which should be reasonably adjusted according to the subsequent alloy addition amount;
[0080] S2. Melting: Put the electrolytic copper into the crucible of the vacuum induction furnace and evacuate to 5.5*10 -4 Pa, and then high-purity argon gas is filled until the pressure in the furnace is 0.04MPa, and then the electric furnace is turned on for heating, and the heating rate is controlled at 10℃ / min. When the temperature reaches 1175℃, the copper begins to melt. After the copper is completely melted, yttrium master alloy, tin ingot and phosphor copper master alloy are added in sequence. After each element is added, an electromagnetic stirring device is used to stir for 11.5 minutes to make the elements fully and evenly melted. Before smelting, a layer of copper needs to be laid on the bottom of the crucible furnace in advance;
[0081] S3, adding carbon nanostructure X: when the temperature of the alloy melt obtained in S2 drops to 1125, the pre-prepared and dispersed carbon nanostructure X dispersion is slowly added to the alloy melt by drip irrigation, and the mixture is continuously stirred for 25 minutes by an electromagnetic stirring device;
[0082] S4, refining: maintain the vacuum degree in the furnace at 5.5*10 -4 Pa, vacuum refining was performed for 17.5 minutes to volatilize and remove the gas and low-melting-point impurities in the alloy liquid;
[0083] S5. Casting: Casting is performed using a water-cooled copper mold, which is preheated to 250° C. before use, and the refined alloy liquid is slowly poured into the mold through the bottom gate, with the pouring speed controlled at 230 mm / s;
[0084] S6. Homogenization treatment: The cast alloy billet is placed in a resistance furnace surrounded by protective gas for homogenization treatment. The heating rate is controlled at 7°C / min. After the temperature is raised to 775°C, it is kept at this temperature for 9 hours. The protective gas is high-purity argon gas, and during the insulation process, the argon gas in the resistance furnace needs to be continuously maintained;
[0085] S7, hot rolling: the alloy billet after homogenization treatment is heated to 875°C for 2 hours to make the alloy billet fully and evenly heated, and then hot rolled on a hot rolling mill, the total processing rate is controlled at 85%, the final rolling temperature is not less than 750°C, during hot rolling, the reduction is controlled at 16% each time, and the rolling pass is determined according to the final size requirements;
[0086] S8, cold rolling: After hot rolling, the strip is pickled and washed, and then cold rolled at room temperature. The total processing rate is controlled at 60%. During cold rolling, the reduction is controlled at 8% each time. During the cold rolling process, multiple intermediate annealing is required. The annealing temperature is 500℃, the holding time is 2 hours, and the furnace gas is protected by high-purity argon. After the cold rolling, low-temperature annealing is carried out at 300℃ and the holding time is 2.25 hours.
[0087] Example 4
[0088] In this embodiment, a vehicle-mounted connector copper alloy strip is provided, wherein the mass percentage composition of the copper alloy strip is: Y: 0.08wt%, Sn: 3wt%, P: 0.06wt%, carbon nanostructure X: 2wt%, and the balance is copper and unavoidable impurities;
[0089] The carbon nanostructure X is a composite of carbon nanotubes and fullerenes, and the mass ratio of the carbon nanotubes to the fullerenes is 3.5:1.
[0090] The preparation method of the copper alloy strip is the same as that of Example 3.
[0091] Example 5
[0092] In this embodiment, a vehicle-mounted connector copper alloy strip has a mass percentage composition of Y: 0.07wt%, Sn: 2.5wt%, P: 0.05wt%, carbon nanostructure X: 1.5wt%, and the remainder is copper and unavoidable impurities;
[0093] The carbon nanostructure X is a composite of carbon nanotubes and fullerenes, and the mass ratio of the carbon nanotubes to the fullerenes is 3:1.
[0094] The preparation method of the above-mentioned vehicle-mounted connector copper alloy strip is the same as that of Example 3.
[0095] Comparative Example 1
[0096] Except for not containing Y, the rest of the formula and preparation process are the same as those of Example 5.
[0097] Comparative Example 2
[0098] Except that the carbon nanostructure X is not contained, the rest of the formula and preparation process are the same as those of Example 5.
[0099] Comparative Example 3
[0100] Except that Y and carbon nanostructure X are not contained, the rest of the formula and preparation process are consistent with those of Example 5.
[0101] Conductivity test
[0102] The copper alloy strips in the above embodiments and comparative examples were prepared into strip samples with a length of 50 mm, a width of 10 mm, and a thickness of 1 mm, and measured using a four-probe resistivity tester. Before the measurement, the surface of the sample was polished with 200-mesh sandpaper to remove the oxide layer and impurities to ensure good electrical contact.
[0103] Place the processed copper alloy strip sample on the test platform of the four-probe resistivity tester to ensure good contact between the sample and the probe. The probe should be evenly distributed on the sample surface and the pressure should be moderate to avoid damage to the sample or affect the measurement results. Set the sample size parameters (thickness, width, etc.) and measurement mode (such as DC four-probe method) on the tester. Start the test program, the instrument begins to measure the resistivity of the sample, and records the measured resistivity value ρ (unit: Ω·m). According to the relationship formula between conductivity σ and resistivity ρ: σ=1 / ρ, calculate the conductivity σ (unit: S / m) of the copper alloy, and then convert it into %IACS value, as shown in Table 1:
[0104] Table 1
[0105] sample Example 1 Example 2 Example 3 Example 4 Example 5 Comparative Example 1 Comparative Example 2 Comparative Example 3 Electrical conductivity (%IACS) 80.5625 80.7 80.936 80.936 84.05 77.02 66.5 65.7
[0106] It can be concluded from the above experimental results that the addition of Y or carbon nanostructure X to the copper alloy strip can significantly improve the electrical conductivity of the copper alloy strip, especially after the addition of both materials, the electrical conductivity is more significantly improved, so that the copper alloy strip can obviously meet the needs of vehicle connectors.
[0107] Corrosion performance test
[0108] According to the copper alloy strip formula described in Examples 1-5 and Comparative Examples 1-3, copper alloy strip samples with uniform size are prepared through corresponding smelting, rolling and other processes. For example, the samples are processed into thin sheets with a size of 1 cm×1 cm and a consistent thickness (such as 2 mm). The surface of each sample is pre-treated by polishing, cleaning and other pretreatments to ensure a uniform surface state for subsequent electrochemical testing.
[0109] A 3.5% NaCl solution (simulating a humid environment containing chloride ions that may be encountered in a vehicle environment) is selected and accurately weighed sodium chloride is dissolved in deionized water to prepare the solution.
[0110] The prepared electrolyte solution is poured into the electrolytic cell, and the three-electrode system is installed in sequence, so that each copper alloy strip sample (as a working electrode) is placed in the electrolytic cell and immersed in the electrolyte solution.
[0111] Connect the electrochemical workstation, turn on the device, select the open circuit potential measurement function, set the measurement time to 60 minutes, and record the change of the open circuit potential of each sample over time during the measurement period. After the potential stabilizes (generally take the potential value in the last stable stage), record the stable open circuit potential value. This value can preliminarily reflect the natural corrosion tendency of the sample in the solution. The more positive the open circuit potential is, the less likely the material is to corrode.
[0112] After completing the open circuit potential measurement, set the polarization curve measurement parameters of the electrochemical workstation for each sample: the scanning potential range is set to be centered on the respective stable open circuit potential and extend 250 mV in the positive and negative directions (which can be adjusted appropriately according to actual conditions); the scanning rate is selected as 0.166 mV / s; and the data acquisition frequency is set to 1 Hz.
[0113] Start the polarization curve measurement program, pay close attention to the changes in current and potential during the measurement process, and after the scan is completed, obtain the polarization curve data (potential-current data pair) corresponding to each copper alloy strip sample.
[0114] The polarization curves were analyzed and processed using the Tafel extrapolation method. The anode and cathode Tafel slopes were fitted using software, and the corrosion current density (i_corr) values corresponding to each sample were calculated based on relevant electrochemical principles. Generally speaking, the smaller the corrosion current density, the better the corrosion resistance of the material.
[0115] The following Table 2 is obtained, recording the open circuit potential value and the calculated corrosion current density value:
[0116] Table 2
[0117] sample Example 1 Example 2 Example 3 Example 4 Example 5 Comparative Example 1 Comparative Example 2 Comparative Example 3 Open circuit potential (V vs SCE) -0.25 -0.20 -0.23 -0.18 -0.15 -0.30 -0.35 -0.40 Corrosion current density (μA / cm²) 2.8 2.2 2.5 2.0 1.8 3.5 4.0 4.5
[0118] It can be seen from the above table that after adding Y or carbon nanostructure X to the copper alloy strip, the corrosion resistance of the copper alloy strip can be significantly improved, especially after the above two components are increased, the corrosion resistance of the copper alloy strip is significantly increased, so that the above copper alloy strip can obviously meet the needs of vehicle connectors.
[0119] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0120] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A copper alloy strip for vehicle connector, characterized in that: The copper alloy strip has a mass percentage composition of 0.04-0.1wt% Y, 1.5-3.5wt% Sn, 0.02-0.08wt% P, 0.5-2.5wt% carbon nanostructure X, and the remainder is copper and unavoidable impurities; The carbon nanostructure X is a composite of carbon nanotubes and fullerenes, and the mass ratio of carbon nanotubes to fullerenes is 2 to 4:1; The preparation method of the carbon nanostructure X is as follows: weigh the carbon nanotubes and fullerenes according to the above ratio, then place them together in an organic solvent, and perform long-term ultrasonic treatment using an ultrasonic dispersion device, the ultrasonic time is 2-4 hours, so that the carbon nanotubes and fullerenes are fully dispersed to form a uniform and stable carbon nanostructure X dispersion liquid, the concentration of which should be reasonably adjusted according to the subsequent alloy addition amount, and then slowly add the pre-prepared and dispersed carbon nanostructure X dispersion liquid into the above alloy melt by drip irrigation.
2. The vehicle-mounted connector copper alloy strip according to claim 1, characterized in that: The copper alloy strip has a mass percentage composition of 0.06-0.08wt% Y, 2-3wt% Sn, 0.04-0.06wt% P, 1-2wt% carbon nanostructure X, and the remainder is copper and unavoidable impurities; The carbon nanostructure X is a composite of carbon nanotubes and fullerenes, and the mass ratio of the carbon nanotubes to the fullerenes is 2.5-3.5:
1.
3. The vehicle-mounted connector copper alloy strip according to claim 1, characterized in that: The copper alloy strip has a mass percentage composition of 0.07wt% Y, 2.5wt% Sn, 0.05wt% P, 1.5wt% carbon nanostructure X, and the remainder is copper and unavoidable impurities; The carbon nanostructure X is a composite of carbon nanotubes and fullerenes, and the mass ratio of the carbon nanotubes to the fullerenes is 3:
1.
4. A method for preparing a vehicle-mounted connector copper alloy strip according to any one of claims 1 to 3, characterized in that: The steps include: S1. Preparation of carbon nanostructure X; S2. Melting: Put the electrolytic copper into the crucible of the vacuum induction furnace and evacuate it to - Pa, and then fill with high-purity argon gas until the pressure in the furnace is 0.03-0.05MPa, then turn on the electric furnace for heating, and control the heating rate at 8-12℃ / min. When the temperature reaches 1150-1200℃, the copper begins to melt. After the copper is completely melted, add yttrium master alloy, tin ingot and phosphor copper master alloy in sequence. After each element is added, use an electromagnetic stirring device to stir for 8-15 minutes to make the elements fully and evenly melted; S3, adding carbon nanostructure X: when the temperature of the alloy melt obtained in S2 drops to 1100-1150° C., an electromagnetic stirring device is used to continuously stir for 20-30 minutes; S4, refining: keep the vacuum degree in the furnace at - Pa, vacuum refining for 15-20 minutes to volatilize and remove the gas and low melting point impurities in the alloy liquid; S5. Casting: Casting is performed using a water-cooled copper mold, which is preheated to 200-300° C. before use, and the refined alloy liquid is slowly poured into the mold through the bottom gate, with the pouring speed controlled at 80-150 mm / s; S6. Homogenization treatment: Place the cast alloy billet into a resistance furnace surrounded by protective gas for homogenization treatment, control the heating rate at 6-8°C / min, heat to 750-800°C, and keep at this temperature for 8-10 hours; S7, hot rolling: heat the alloy billet after homogenization treatment to 850-900℃ for 1.5-2.5 hours to make the alloy billet fully and evenly heated, and then hot roll it on a hot rolling mill, with the total processing rate controlled at 80-90%, and the final rolling temperature not less than 750℃; S8. Cold rolling: After the hot-rolled strip is pickled and washed, it is cold rolled at room temperature. The total processing rate is controlled at 50-70%. During cold rolling, the reduction is controlled at 6-10% each time.
5. The method for preparing a copper alloy strip for a vehicle connector according to claim 4, characterized in that: In step S1, the organic solvent is N-methylpyrrolidone or dimethylformamide.
6. The method for preparing a copper alloy strip for a vehicle connector according to claim 4, characterized in that: In step S2, a layer of copper needs to be laid on the bottom of the crucible before smelting.
7. The method for preparing a vehicle-mounted connector copper alloy strip according to claim 4, characterized in that: In step S6, high-purity argon is used as the protective gas, and the argon in the resistance furnace needs to be continuously maintained during the insulation process.
8. The method for preparing a vehicle-mounted connector copper alloy strip according to claim 4, characterized in that: In step S7, during hot rolling, the reduction amount is controlled at 12-20% each time, and the rolling passes are determined according to the final size requirements.
9. The method for preparing a vehicle-mounted connector copper alloy strip according to claim 4, characterized in that: In step S8, during the cold rolling process, multiple intermediate annealings are required, the annealing temperature is 450-550°C, the insulation time is 1.5-2.5 hours, and the gas in the furnace is protected by high-purity argon.
10. The method for preparing a vehicle-mounted connector copper alloy strip according to claim 4, characterized in that: After step S8 is completed, a low-temperature annealing treatment is performed, the annealing temperature is 250-350° C., and the insulation time is 1.5-3 hours.
Citation Information
Patent Citations
Batch preparation method of nano-carbon reinforced copper-based composite material
CN112011705A
Cu-sn-p-based copper alloy sheet material and its production method, and connector
JP2009079270A